2011
DOI: 10.1111/j.1654-1103.2011.01274.x
|View full text |Cite
|
Sign up to set email alerts
|

Hypothesis‐driven species distribution models for tree species in the Bavarian Alps

Abstract: Question: What are the main drivers for tree species distribution in the Bavarian Alps? What are the species-specific habitat requirements? Are predictions in accordance with expert knowledge?Location: Bavarian Alps (Southern Germany).Methods: To describe tree species-environment relationships, we established species distribution models for the 14 most common tree species of the region. We combined tree species occurrence data from forest inventories and a vegetation database with environmental data from a dig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
46
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(49 citation statements)
references
References 44 publications
(57 reference statements)
2
46
1
Order By: Relevance
“…Also, our results agreed with many other studies with regards to the importance of temperature [23,25] and rainfall [23,28,37], in modelling the distribution of tree group species.…”
Section: Climatesupporting
confidence: 82%
See 2 more Smart Citations
“…Also, our results agreed with many other studies with regards to the importance of temperature [23,25] and rainfall [23,28,37], in modelling the distribution of tree group species.…”
Section: Climatesupporting
confidence: 82%
“…The results which predicted the spatial distribution of tree species using the climatic variables group showed that all three variables-temperature, evapo-transpiration and rainfall-were significant parameters in modelling the distribution of tree species, and agreed with the results of [25,33]. Also, our results agreed with many other studies with regards to the importance of temperature [23,25] and rainfall [23,28,37], in modelling the distribution of tree group species.…”
Section: Climatesupporting
confidence: 82%
See 1 more Smart Citation
“…See, e.g., Austin and Smith (1987), Austin (2002), Mellert et al, (2011). The early applications of species modeling tended to focus on explanation ).…”
Section: > Plot(predictors)mentioning
confidence: 99%
“…But at local to landscape scales, disturbances, species interactions and direct physiologically effective parameters control the occurrence of plant species and plant communities. Variables influencing vegetation distribution can be broadly related to moisture, energy, nutrient availability and geomorphodynamics (Mellert et al, 2011). To study drought or aridity-induced vegetation limits, moisture supply is the main factor to be considered.…”
Section: Vegetation Assessment In the Fieldmentioning
confidence: 99%